Nature Rx : improving college-student mental health - Rakow, Donald Andrew, 1951-; Eells, Gregory T., 1967-2019 (Comstock Publishing Associates, an imprint of Cornell University Press, 2019)
While ensuring the mental health of students is an increasing challenge for college and university administrators and counseling centers, this book explores how Nature Rx programs can be a key component of a comprehensive wellness system. --